Effect of the plantation age on the use of Eucalyptus stands by medium to large-sized wild mammals in south-eastern Brazil - Timo, TP; Lyra-Jorge, MC; Gheler-Costa, C; Verdade, LM (IForest (Viterbo), 2015)
In São Paulo State, in Southeastern Brazil, the Eucalyptus plantations have been replacing large areas which were formerly occupied by pastures used for livestock production. Such land use change may affect the habitat use by wildlife in these anthropic landscapes. In this region, the commercial Eucalyptus plantations of the paper and cellulose industry usually take from 6 to 7 years to be harvested. During its production cycle, the Eucalyptus stands vary from an open savanna-like environment just after plantation, when plants still resemble bushes, to a forest-like environment with densely distributed 18-meter high trees. Previous studies show that the Eucalyptus plantations in Southeastern Brazil are used by generalist species including medium and large sized mammals. However, the possible influence of such dramatic temporal environmental heterogeneity on the wildlife habitat use in Eucalyptus plantations is still unknown. In this study, which follows a classic stratified design, we evaluate the influence of the Eucalyptus stand age on the local patterns of distribution and abundance of middle to large-sized wild mammals. Our results show an increase not only in their species richness, but also in their frequency of occurrences along the commercial cycle of the Eucalyptus plantations with a steep decline in both before harvest. This pattern may be related to weed control practices which significantly reduce the understory vegetation, in especial at the end of the commercial cycle while preparing for harvest. Future studies should prioritize the possible variation on the trophic structure in the Eucalyptus plantations along commercial cycles as a response of wildlife friendly silvicultural/agricultural management practices.